2020
DOI: 10.3390/jcm9113574
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy of the Corneal-Conjunctival Transition in the Evaluation of Epithelial Renewal after SLET

Abstract: Examination of the corneal surface by in vivo confocal microscopy (IVCM) allows for objective identification of corneal and conjunctival cell phenotypes to evaluate different epithelialization patterns. Detection of a corneal-conjunctival epithelial transition could be considered as a sign of restored epithelial function following simple limbal epithelial transplantation (SLET). This is a prospective, interventional case series. We assessed patients with limbal stem cell deficiency (LSCD) by IVCM, preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Also, while no transition zone between the corneal and conjunctival epithelium was noted in 2 out of 4 quadrants (i.e., inferior-nasal and inferior-temporal), 6 the sub-basal nerve plexus showed a reduced corneal nerve density in all the analyzed sectors.…”
Section: Case Reportmentioning
confidence: 79%
See 2 more Smart Citations
“…Also, while no transition zone between the corneal and conjunctival epithelium was noted in 2 out of 4 quadrants (i.e., inferior-nasal and inferior-temporal), 6 the sub-basal nerve plexus showed a reduced corneal nerve density in all the analyzed sectors.…”
Section: Case Reportmentioning
confidence: 79%
“… 12 Also, due to their ability at inducing limbal stem cell (LSC) migration, inhibiting cellular apoptosis, and at maintaining epithelial progenitor cells within the LSC niche, recent studies have identified h-AMs as useful scaffolds to be applied to the field of corneal tissue engineering. 6 , 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laser focusing principle of IVCM is used to scan each point of the detected layer in the confocal plane. In IVCM, the formation of ocular surface tissues can be observed at multiple levels, and the cell level of tissue morphology and changes can be photographed in real time 4 . Hence, IVCM has real-time, non-invasive, three-dimensional advantages.…”
Section: Introductionmentioning
confidence: 99%